Crystal magic for the modern witch - Hunter, Devin, 1986- (Llewellyn Publications, 2022)
"Crystal Magic for the Modern Witch presents detailed information on 100 crystals, gems, and metals, from their physical, mental, and spiritual benefits to vibrational keywords and origin countries. Find out what element, tarot card, affirmation, plants, and planets are associated with each crystal. Discover how to cleanse and program a crystal, create gem elixirs, and communicate with different kinds of crystal-aligned spirits. Using photographs taken by the author. this guide also provides dozens of spells and workings for protection, well-being, success, and divination"--